The reasonable therapeutic modality for biliary duct-to-duct anastomotic stricture after liver transplantation: ERCP or PTC? - Bowen, Hu; Wenzhi, Guo; Peihao, Wen; Jihua, Shi; Shuijun, Zhang (Frontiers in Oncology, 2022)
Objective: To compare the initial success rate, feasibility, and effectiveness of endoscopic retrograde cholangiopancreatography (ERCP) versus percutaneous transhepatic cholangiography (PTC) for anastomotic biliary stricture after liver transplantation (LT). Methods: We retrospectively analyzed the data collected during January 2015 to December 2021 from liver transplantation recipients who developed anastomotic biliary stricture after liver transplantation and treated by ERCP and/or PTC. The success rate, complications and patients’ survival rate of ERCP and PTC procedures was evaluated. Results: Forty-eight patients who underwent LT and were confirmed to have the anastomotic biliary stricture were enrolled. Overall, 48/48 patients underwent single or multiple ERCP procedures as the first line therapy; 121 therapeutic ERCPs (3.36 ± 2.53 ERCPs per patient) were performed in 36/48 patients successfully. All the 12 patients who failed ERCP tend to have special bile duct conditions such as overlong, angle shaped, and/or extremely narrowed bile duct and underwent PTC as an alternative treatment. The initial success rate of ERCP was 75% (36/48) while the success rate of ERCP for the 12 patients with special bile duct was 0% (0/12). PTC was an effective second-line treatment for those 12 patients who failed ERCP, and 58.33% (7 of 12 cases) were treated successfully. The average procedure time in PTC group was significantly lower than ERCP group (t=2.292, P=0.027). The feasibility of ERCP was associated with the anatomical shape of bile duct and the severity of the stricture site. Finally, the cumulative survival rate was 100% (12/12) in PTC group compared to 86.11% (31/36) in ERCP group (2=0.670, P=0.413). Conclusion: ERCP is the gold standard method for the diagnosis and effective intervention for the management of biliary complications after LT. However, its use in certain types of biliary complications is not promising and associated with significant risk. PTC and other interventions should be studied along with ERCP for patients for whom ERCP may not work. The feasibility and efficacy of primary management can be predicted by the noninvasive imaging examinations like MRCP before the procedure, which may help with the choice of the most reasonable therapeutic modality and avoiding unnecessary financial burden and complications.